Data visualization for text-based documents - Yong, Chung Wei (2023)
This paper examines the availability, and needs of simple, easy to use, and easy to install data visualization and debugging software. Recently, the prominent rise of the Internet of Things, and Artificial Intelligence has caused an increase of interest and research projects in big data. Along with this, there is an increased demand for simple and easy to use visualization tools to assist in research. Among these sources of demand is Dr. Ooi Boon Yaik, a researcher and lecturer at University Tunku Abdul Rahman who is running quite a few research projects that need these simple to use tools. Incorporating various web technologies, and software tools, this project aims to produce a tool that fills a niche that has not yet been done but greatly needed by researchers. Which is, a data visualisation and debugging tool that is lightweight, easy to use, simple and customizable.